Особливості сталого розвитку аграрного сектору та його нормативно-правове забезпечення - Страпчук, Світлана Іванівна; Strapchuk, Svitlana (My University, 2021)
У статті проаналізовані погляди науковців-економістів щодо особливостей сталого розвитку в аграрному секторі та здійснено систематизацію його нормативно-правового забезпечення. Проведений аналіз наукових публікацій дозволив підкреслити роль економічної складової сталого розвитку в триєдиній концепції, яка є динамічною системою, здатною змінювати рівень свого гомеостазу, стимулювати розвиток ресурсозберігаючих технологій та реагувати на обмеження. Аграрний сектор має враховувати тенденції, що склалися на споживчому ринку та ефективно реагувати на зміну міжнародних агрокультурних політик. Дослідження правового забезпечення аграрного сектору дало змогу систематизувати законодавчі акти щодо врегулювання питань сталого розвитку традиційного сільськогосподарського виробництва, його альтернативних форм та використання біотехнологій в процесі діяльності підприємств. The article analyses the views of economists on the peculiarities of sustainable development in the agricultural sector and systematises its regulatory and legal support. The analysis of scientific publications allows to emphasize the role of the economic component of sustainable development in the triune concept, which represents a dynamic system that can change the level of its homeostasis, stimulate the development of resource-saving technologies and respond to constraints. The agricultural sector must take into account the trends in the consumer market and respond effectively to changes in international agricultural policies. The study of legal support for sustainable development of the agricultural sector made it possible to systematise legislation aimed at regulating traditional agricultural production, its alternative forms and the use of biotechnology in the business activity of enterprises. It has been established that ensuring the growth of agricultural production with a simultaneous transition to sustainable development is possible by addressing the risks associated with biodiversity loss, soil pollution, excessive fresh water consumption, etc. The importance of regulating food safety, which is an incentive for the transition to a balanced diet is substantiated. The main tools for implementing the principles of sustainability are effective regulatory support aimed at supporting and developing the agricultural sector, and economic incentives of pricing and fiscal policies. Thus, the contribution of the study is a detailed analysis of economists’ views on the problem of sustainable development of agricultural production in combination with the analysis of existing legal support, which aims to anticipate potential risks to human life and health, environment, biodiversity, etc.
Pecularities of sustainable development in the agricultural sector and its regulatory and legal support
Страпчук С.І., канд. екон. наук, доцент
Keywords: Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::SOCIAL SCIENCES::Business and economics; сталий розвиток; аграрне виробництво; нормативно-правове забезпечення; традиційна та альтернативні форми ведення сільського господарства; ГМО; sustainable development; agricultural production; legal support, traditional and alternative forms of agriculture; GMOs